PERANCANGAN SISTEM INFORMASI AKUNTANSI DENGAN AKAD IJARAH PADA HOTEL SYARIAH DI BANDUNG - Indri Yuliafitri; Euis Nurhayati; Gia Kardina Prima A (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2019)
[English] This study aims to determine the accounting information system currently used by sharia hotels in Bandung and design accounting information system at sharia hotel in Bandung. This research is a type of research and development. The method used is in-depth interviews to Sharia Hotels